Life-Long Wheel Running Attenuates Age-Related Fiber Loss in the Plantaris Muscle of Mice: a Pilot Study - Suwa, M.; Ishioka, T.; Kato, J.; Komaita, J.; Imoto, T.; Kida, A.; Yokochi, T. (International Journal of Sports Medicine, 2016)
The purpose of this study was to investigate whether long-term wheel running would attenuate age-related loss of muscle fiber. Male ICR mice were divided into young (Y, n=12, aged 3 months), old-sedentary (OS, n=5, aged 24 months), and old-exercise (OE, n=6, aged 24 months) groups. The OE group started spontaneous wheel running at 3 months and continued until 24 months of age. Soleus and plantaris muscles were fixed in 4% paraformaldehyde buffer. The fixed muscle was digested in a 50% NaOH solution to isolate single fiber and then fiber number was quantified. The masses of the soleus and plantaris muscles were significantly lower at 24 months than at 3 months of age, and this age-related difference was attenuated by wheel running (P<0.05). Soleus muscle fiber number did not differ among the groups. In the plantaris muscle, the fiber number in the OS group (1 288±92 fibers) was significantly lower than in the Y group (1 874±93 fibers), and this decrease was attenuated in the OE group (1 591±80 fibers) (P<0.05). These results suggest that age-related fiber loss occurs only in the fast-twitch fiber-rich muscle of mice, and that life-long wheel running exercise can prevent this fiber loss.
Keywords: exercise; muscle fiber loss; sarcopenia; skeletal muscle; training